Remaking reality : nature at the millenium - Braun, Bruce, 1964-; Castree, Noel, 1968- (Routledge, 1998)
"This book rejects apocalyptic pronouncements that the end of the millennium represents the 'end' of nature as well. Remaking Reality brings together contributors from across the human sciences who argue that a notion of 'social nature' provides great hope for the future. Applying a variety of theoretical approaches to social nature, and engaging with debates in politics, science, technology and social movements surrounding race, gender and class, the contributors explore important and emerging sites where nature is now being remade with considerable social and ecological consequences."--Publisher description